(untitled) (SCIENCE TIME JOURNAL, 2026)
The development of receptive speech abilities in English, the modernisation of new activities including the use of contemporary pedagogical technology, and the enhancement of students’ professional competence in foreign languages are all covered in this article. The purpose of this piece is to clarify how teachers will retain the exercises sufficiently to feel comfortable utilising them with their pupils whilst modifying their capacity to complete them. The idea that teachers’ professional development is dependent on obtaining new knowledge and resources from other sources is more significant since it discourages instructors from feeling in control of their own professional growth.